2010
DOI: 10.1016/j.labeco.2009.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Tax policy and returns to education

Abstract: This paper considers how asymmetric tax treatment, where labour market earnings are taxed but household production is untaxed, affects educational choice and labour supply. We show that taxes on labour market earnings can generate a large (non-marginal) switch to home production and the ensuing deadweight losses are large. Using a cross-country panel, we find that gender differences in labour supply responses to tax policy can explain differences in aggregate labour supply and years of education across countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…Cross-country differences may also reflect the variety of provisions that are made for looking after dependents, especially children (Gash, 2008;Jaumotte, 2003). Analysing OECD data, Booth and Coles (2010) find a positive correlation between public spending on childcare and women's labour force participation. Public policies aimed at developing part-time employment, particularly in the northern European countries, could thus also be grounded in the objective of enhancing family welfare through the reconciliation of work and family (Thurman and Trah, 1990).…”
Section: Institutional and Regulatory Factorsmentioning
confidence: 96%
“…Cross-country differences may also reflect the variety of provisions that are made for looking after dependents, especially children (Gash, 2008;Jaumotte, 2003). Analysing OECD data, Booth and Coles (2010) find a positive correlation between public spending on childcare and women's labour force participation. Public policies aimed at developing part-time employment, particularly in the northern European countries, could thus also be grounded in the objective of enhancing family welfare through the reconciliation of work and family (Thurman and Trah, 1990).…”
Section: Institutional and Regulatory Factorsmentioning
confidence: 96%
“…The total available budget is fully spent on saving  , ways of subsidies on education are specified (e.g., (Blankenau and Simpson, 2004;Bovenberg and Jacobs, 2005;Booth and Coles, 2010)). The education cost of the representative household equals the education price charged by the education sector minus the subsidy from the government…”
Section: Current and Disposable Incomesmentioning
confidence: 99%
“…By being less likely to supply their skills in the labour force, they may be deterred from investing in skills in the first place. Indeed, Booth and Coles (2010) found that, on average across 20 OECD countries, 19 average years of female education are negatively associated (at a statistically significant level) with the tax wedge on secondary earners -an indicator developed by the authors to measure the "marriage penalty" of family-based taxation. 20 The choice to support horizontal equity through joint family taxation must therefore be balanced against any negative efficiency implications in terms of labour supply and human capital accumulation.…”
Section: Efficiency-equity Trade-offsmentioning
confidence: 99%